Functional characterization of the MSP-C6 promoter as a potential tool for mesocarp-preferential expression of transgenes - Badai, Siti Suriawati; Abd Rasid, Omar; Abdul Masani, Mat Yunus; Kuang, Lim Chan; Pek, Lan Chan; Shaharuddin, Noor Azmi; Abdullah, Mohd Puad; Ahmad Parveez, Ghulam Kadir; Chai, Ling Ho (Elsevier GmbH, 2023)
Modification of lipid composition in the mesocarp tissue of oil palm involves genetic manipulation of multiple genes. More than one mesocarp-preferential promoter is necessary for the expression of individual transgenes in the same plant to obviate transcriptional gene silencing. This study aimed to identify genes that are preferentially expressed in the mesocarp tissue and characterize selected candidate mesocarp-preferential promoters. Ten transcripts that were preferentially expressed in the mesocarp tissue were identified from the analysis of 82 transcriptome datasets of 12 different oil palm tissues. The expression of two candidate genes, MSP-C1 and MSP-C6, was verified to be preferentially expressed in the mesocarp tissues and shown to have a low expression level in non-mesocarp tissues by reverse transcription quantitative real-time PCR (RT-qPCR). MSP-C6 promoter fragments of different lengths were transformed into tomato plants for further characterization. Both unripe and ripe fruits of transgenic tomato plants transformed with a construct harboring the MSP-C6-F1 (2014 bp) promoter were shown to have high beta-glucuronidase (GUS) activities. The findings of this study suggest the potential applications of the MSP-C6 promoter as a molecular tool for genetic engineering of novel traits in fruit crops.